2008
DOI: 10.1080/08860220701810364
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between the MEFV Genotype, Clinical Features, and Cytokine-Inflammatory Activities in Patients with Familial Mediterranean Fever

Abstract: Familial Mediterranean Fever (FMF) is an autosomal recessive disease characterized by periodic attacks of fever and polyserositis. The effects of the MEFV genotype differences on clinical picture and inflammatory activity have not been well documented. The aim of this study was to investigate levels of conventional inflammation markers, procalcitonin, interleukin levels, TNF-alpha, and C5a levels in patients with FMF who had different MEFV genotypes and compare them with those of healthy subjects. The study co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 13 publications
1
12
0
1
Order By: Relevance
“…There were no patients in current study with amyloidosis, and all patients were in the attack-free period. Subclinical inflammation and an increase in acute-phase proteins in the symptom-free period has been reported in FMF (9)(10)(11). The detection of a high N/L ratio in the current study during the attack-free period supports these findings.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…There were no patients in current study with amyloidosis, and all patients were in the attack-free period. Subclinical inflammation and an increase in acute-phase proteins in the symptom-free period has been reported in FMF (9)(10)(11). The detection of a high N/L ratio in the current study during the attack-free period supports these findings.…”
Section: Discussionsupporting
confidence: 81%
“…These parameters are also indicative of systemic inflammation (7). It was shown that inflammation continues not only during attacks but also during symptom-free periods (8)(9)(10)(11). The neutrophil/lymphocyte (N/L) ratio can be easily obtained from the differential white blood cell (WBC) count and has been studied in the context of many diseases (12)(13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…In a cohort study by Salah et al (26), cardiac involvement appeared to be common in children with FMF, and pericardial effusions were significantly related to the presence of mutation types E148Q, P369S, and V726A. The M694V mutation of the MEFV gene has been found to be associated with a complicated clinical course and increased sensitivity to inflammatory disorders and cardiac involvement (27). It has also been suggested that MEFV mutations in early coronary heart disease patients was significantly increased in contrast to coronary heart disease patients and healthy controls (28).…”
Section: Discussionmentioning
confidence: 99%
“…It is shown that chronic inflammation leads to a decrease in BMD in various studies (Gough et al 1994;La Montagna et al 1995;Carbone et al 1999;Harrison et al 2002). Recent studies have shown that subclinical inflammation may continue in some FMF cases, even in the symptom-free periods (Tunca et al 1999;Duzova et al 2003;Lachmann et al 2006;Colak et al 2008). The continuous subclinical inflammation in FMF patients may lead to osteoporosis in this group of patients.…”
mentioning
confidence: 99%